Observed Classroom Quality During Teacher Education and Two Years of Professional Practice - Malmberg, L; Hagger, H; Burn, K; Mutton, T; Colls, H (2010)
The aims of the present study are to investigate whether and how teachers change in their observed classroom quality (emotional and instructional support, classroom organization, and students' engagement; measured with the Classroom Assessment Scoring System observation measure for secondary school [CLASS-S]; Pianta, La Paro, and Hamre, 2006) during their teacher education year and the first 2 years of professional practice, as well as the effects of personal characteristics and contextual factors on observed classroom quality. Confirmatory factor analyses (CFAs) with a reduced number of indicators per a priori construct fitted the data well. Using factor scores in 3-level multilevel models for change (376 lesson segments 20 min in duration nested within 10 time points, within 17 teachers), we found more variability over time than within lessons and the least variability between teachers. Emotional support showed an inverted U-shaped change over time, whereas classroom organization increased linearly over time. Emotional support was lower for older students, and students were more engaged in larger classes. A higher level of classroom organization during lessons was related to less variability in student engagement, but variability of instructional support was unrelated to variability of student engagement within each lesson. The findings are discussed within the context of teachers' supported transitions into professional practice. © 2010 American Psychological Association.